2019
DOI: 10.1017/s0954394519000085
|View full text |Cite
|
Sign up to set email alerts
|

Compression in the California Vowel Shift: Tracking generational sound change in California's Central Valley

Abstract: ABSTRACTThis paper investigates the California Vowel Shift, previously characterized as a chain shift, in communities across California's Central Valley. An incremental apparent time analysis of 72 Californians’ vowel spaces provides no clear evidence of a gradual chain shift; that is, changes have not unfolded in an order that reflects an implicational chain in chronological time. Instead, we see contemporaneous movements of vowels that work against the phonological tendency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 50 publications
2
41
0
Order By: Relevance
“…Further, while some have noted that the directionality of NCS reversal matches the “Third Dialect Shift,” proposing orientation to this supralocal standard as a driver of reversal (e.g. Wagner et al, 2016), almost none of our younger speakers produce absolute vowel spaces that look or sound like speakers in “Third Dialect Shift” locales, like California (D’Onofrio et al, 2019). We propose that a localized view of the evolving dynamics of migration, social contact, and attitudes in this particular community better motivates the observed sound change reversal.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Further, while some have noted that the directionality of NCS reversal matches the “Third Dialect Shift,” proposing orientation to this supralocal standard as a driver of reversal (e.g. Wagner et al, 2016), almost none of our younger speakers produce absolute vowel spaces that look or sound like speakers in “Third Dialect Shift” locales, like California (D’Onofrio et al, 2019). We propose that a localized view of the evolving dynamics of migration, social contact, and attitudes in this particular community better motivates the observed sound change reversal.…”
Section: Discussionmentioning
confidence: 80%
“…Driscoll & Lape, 2015) or matched guise tasks (Thiel & Dinkin, 2017). Notably, the reversal of the NCS constitutes the same directional shifts (TRAP and DRESS backing/lowering, LOT backing) observed in the so‐called “Third Dialect” or “Elsewhere” shift, a cross‐regional movement of vowels observed across swaths of North America, including Canada and the US West and Midlands (Boberg, 2005; D’Onofrio, Pratt, & Van Hofwegen, 2019; Durian, 2012). Because of the similarity between NCS reversal and the “Third Dialect” shift, some have suggested that younger, upwardly mobile speakers in the Inland North are moving away from the NCS to express an orientation toward this “standard” supralocal sound change (e.g.…”
Section: Introductionmentioning
confidence: 96%
“…This argument appears to find support in studies that document less extreme LBMS than in California, that is, those studies that find that bat backing is the most robust change in progress while bet and bit show only partial change (Hall-Lew et al 2015;Becker et al 2016;Swan 2016; Fridland and Kendall 2017). However, it is unclear whether these results demonstrate that these locales "lag behind" the California data, where sound change is also still in progress in both urban coastal areas (Kennedy and Grama 2012;Grama and Kennedy 2019 [this volume]) and in rural inland areas (Podesva et al 2015;D'Onofrio, Pratt, and Van Hofwegen 2019). Other scholars have even argued for diffusion in the opposite direction, Introduction et al 2017), and in New Mexico, where Anglo women are leading in rotation for both bat and bet, though there is no apparent-time evidence of bit lowering (Brumbaugh and Koops 2017).…”
Section: The Beginning Of the Story : The C Alifornia And C Anadian Vmentioning
confidence: 99%
“…More recent research has documented the LBMS in inland, rural areas. Though the shift is less advanced, young people and women lead, indicating change in progress (Podesva et al 2015;D'Onofrio et al 2016;D'Onofrio, Pratt, and Van Hofwegen 2019). In addition, research into perceptions of aspects of the LBMS, specifically bat backing, have demonstrated the feature's indexicality at various levels, including region (California, for both listeners within and outside the state), personae (the stereotyped "Valley Girl" as well as a "Business Professional" persona), and attributes like confidence and prestige (D'Onofrio 2015; Villareal 2018; Villareal and Kohn, forthcoming).…”
Section: The Beginning Of the Story : The C Alifornia And C Anadian Vmentioning
confidence: 99%
See 1 more Smart Citation